2016
DOI: 10.1200/jco.2016.34.3_suppl.259
|View full text |Cite
|
Sign up to set email alerts
|

Survivors preferences about the role of the oncologist and primary care provider.

Abstract: 259 Background: Oncologist and Primary Care Provider are both involved in cancer patients follow-up. Patient's preference is an important issue. Aims This observational study was made to investigate: a) if and how long after the diagnosis the patient prefers to be followed by PCPs, Oncologist or both; b) if they prefer to be followed in the same institute where they received acute phase care; c) if it's important to receive recommendations about their lifestyle. Methods: 150 patients were recruited between Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In particular, no previous studies have reported survivors’ rates of regular primary care visits; we found that 72.7% of our sample reported regular primary care visits. It is possible that patients preferred to see an oncology clinician due to greater perceived competence and expertise in cancer survivor care (Tralongo et al, 2016). However, ongoing healthcare visits with a primary care provider throughout the cancer care trajectory are important for health monitoring and management of other health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, no previous studies have reported survivors’ rates of regular primary care visits; we found that 72.7% of our sample reported regular primary care visits. It is possible that patients preferred to see an oncology clinician due to greater perceived competence and expertise in cancer survivor care (Tralongo et al, 2016). However, ongoing healthcare visits with a primary care provider throughout the cancer care trajectory are important for health monitoring and management of other health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…14 Some studies have shown that cancer survivors have similar needs and preferences for follow-up to some extent due to the similarity of disease characteristics and treatment processes. [15][16][17][18][19][20][21][22][23] Therefore, understanding the follow-up service preferences of Chinese gastric cancer survivors has reference value and guidance significance for the development of global follow-up service strategies. In DCEs, follow-up service-related attributes and levels are the key to assessing individual preferences for gastric cancer survivors.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%